2003
DOI: 10.1016/s0002-9149(02)02998-3
|View full text |Cite
|
Sign up to set email alerts
|

QTc-prolonging drugs and hospitalizations for cardiac arrhythmias

Abstract: Cardiac arrhythmia as an adverse effect of noncardiac drugs has been an issue of growing importance during the past few years. In this population-based study, we evaluated the risk for serious cardiac arrhythmias during the use of several noncardiac QTc-prolonging drugs in day-to-day practice, and subsequently focused on several specific groups of patients who could be extremely vulnerable for drug-induced arrhythmias. We performed a case-control study in which patients (cases), hospitalized for nonatrial card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 31 publications
2
14
0
Order By: Relevance
“…A finding consistent with other studies on the association between QTc-prolonging drugs and cardiac arrhythmias is that there appears to be a positive doseresponse relationship [3,6,[16][17][18][19]. In accordance with Ray et al [20], we found that cytochrome P450 pharmacokinetic drug-drug interactions apparently play an important role.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…A finding consistent with other studies on the association between QTc-prolonging drugs and cardiac arrhythmias is that there appears to be a positive doseresponse relationship [3,6,[16][17][18][19]. In accordance with Ray et al [20], we found that cytochrome P450 pharmacokinetic drug-drug interactions apparently play an important role.…”
Section: Discussionsupporting
confidence: 93%
“…A finding consistent with other studies on the association between QTc‐prolonging drugs and cardiac arrhythmias is that there appears to be a positive dose–response relationship [3, 6, 16–19]. In accordance with Ray et al.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, most studies on drug‐induced QTc prolongation have focused on the risk of QTc prolongation and TdP when using only one QTc‐prolonging drug. It is not known whether combining two or more QTc‐prolonging drugs leads to a cumulative or perhaps even synergistic prolongation of the QTc interval .…”
Section: Introductionmentioning
confidence: 99%
“…4 The most widely used antiarrhythmic drugs, for example, amiodarone/dronedarone 5 are efficacious but are nonselective and inhibit ion channels, which are expressed in the human atrium and ventricle. Agents that inhibit ion channels that prolong ventricular effective refractory period have the potentially life threatening arrhythmia torsades de pointe, 6 and therefore, administration of nonselective drugs is often limited to a hospital setting with monitoring. There is currently an unmet medical need for agents that effectively restore NSR and have an increased margin for safety for the treatment of AF.…”
Section: * S Supporting Informationmentioning
confidence: 99%